2019
DOI: 10.1002/acs.2993
|View full text |Cite
|
Sign up to set email alerts
|

Flexible noncontact electrodes for comfortable monitoring of physiological signals

Abstract: KEYWORDS capacitive coupling, flexible noncontact electrode, long-term healthcare monitoring, physiological signals, wearable devices Shuting Liu and Mingxing Zhu have equal contributions to the work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…As the thickness of the insulating layer increases, the signal quality decreases. In theory, the further the electrode is from the source, the smaller the coupling signal ( Liu et al, 2019 ). In this experiment, we used two thicknesses of clothing for monitoring and both obtained an effective ECG signal, namely one layer and three layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the thickness of the insulating layer increases, the signal quality decreases. In theory, the further the electrode is from the source, the smaller the coupling signal ( Liu et al, 2019 ). In this experiment, we used two thicknesses of clothing for monitoring and both obtained an effective ECG signal, namely one layer and three layers.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a flexible non-contact electrode for WBS was proposed based on the principle of capacitive coupling for physiological signal acquisition. The electrode was built with flexible printed circuits (FPC) materials and could be bent to ensure better capacitive coupling with the skin ( Yi et al, 2018 ; Liu et al, 2019 ). Although the motion had a great influence, the proposed non-contact electrode could acquire high-quality ECG compared with the wet electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a band-pass filter was used to mitigate motion noise, resulting in the electrode demonstrating exceptional performance. This was substantiated by the acquisition of high-fidelity EMG data during the flexion or extension of the brachial muscles (Liu et al , 2019).…”
Section: Classification Of Vital Signs In Wearable Sensingmentioning
confidence: 99%
“…The system can effectively distinguish between an open or closed hand as the electrodes were placed on the arm. Since then, they added a band-pass filter to filter motion noise and found that the electrode showed an excellent performance, which was evidenced by the high-quality EMG signals obtained during the opening or closing of the upper arm muscles [ 54 ].…”
Section: Bioelectrical Signalsmentioning
confidence: 99%